2019
DOI: 10.1002/pbc.27765
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical activity of the antibody‐drug conjugate denintuzumab mafodotin (SGN‐CD19A) against pediatric acute lymphoblastic leukemia xenografts

Abstract: Background Denintuzumab mafodotin (SGN‐CD19A) is a CD19‐targeting antibody‐drug conjugate, comprising a monoclonal antibody conjugated to the potent cytotoxin monomethyl auristatin F. Since denintuzumab mafodotin has previously shown activity against B‐cell malignancies in early‐stage clinical trials, it was of interest to test it against the Pediatric Preclinical Testing Program preclinical models of CD19+ pediatric acute lymphoblastic leukemia (ALL). Procedures Denintuzumab mafodotin was evaluated against ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This PDF file includes: Materials and Methods Figs. S1 to S30 Tables S1 to S10 References (75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86) Other Supplementary Material for this manuscript includes the following: Data…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…This PDF file includes: Materials and Methods Figs. S1 to S30 Tables S1 to S10 References (75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86) Other Supplementary Material for this manuscript includes the following: Data…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Jones et al proved that SGN-CD19A is an active therapy against pediatric ALL-patient-derived xenografts. However, the denintuzumab mafodotin preclinical activity levels did not outperform those achieved with vincristine as a single agent [ 196 ].…”
Section: Future Perspectives In the Treatment Of All Or Amlmentioning
confidence: 99%
“…In a preclinical study, denintuzumab mafodotin showed single-agent efficacy against eight pediatric precursor B-cell lineage ALL patient-derived xenografts, and results from the corresponding clinical trials are anticipated [ 36 ]. Another anti-CD19 mAb named B43 conjugated with the tyrosine kinase inhibitor (TKI) genistein has entered clinical trials in children with r/r ALL and non-Hodgkin’s lymphoma (NHL), but no results were found in the literature search.…”
Section: Targeting Antigens On Lymphoid Cellsmentioning
confidence: 99%